The Safety Threshold of Vietnam's Banks During Covid-19 - Xuan, Pham Thi Thanh; Nguyen, Trung Duc; Tin, Ho Huu; Huyen, Le Thi Thanh (University of Merdeka Malang, 2021)
Using the stress test, we measured the Comercial banks' withstand under pressure caused by the outbreak of COVID-19, which led to a freeze of the real estate market, a fall of the stock market, and an increase of non-performing loans (NPLs). The findings show positive and hopeful signs. Even though the real estate and stock markets fell by 40%, resulting in a significant devaluation of the banks' loan collaterals, banks do not need to supplement provisions for credit risk. The high number of NPLs, which lead to increased provisioning, erodes net earnings, reducing the capital adequacy ratio (CAR). Banks can still meet both the 9% minimum CAR requirement and the 3% maximum NPL requirement. The study also identifies the maximum safety threshold of the Vietnamese banking system, which averaged up to a 50% increase in NPLs. Two of the country's top 10 banks are even able to maintain a CAR greater than 9% and an NPL ratio below 3%, although NPLs increase to 450% and 215% compared to these before the shock, respectively.JEL: E50, G21